Injury reduction programs for reducing the incidence of sport-related head and neck injuries including concussion: a systematic review - Elliott, J.; Heron, N.; Versteegh, T.; Gilchrist, I. A.; Webb, M.; Archbold, P.; Hart, N. D.; Peek, K. (Sports Medicine, 2021)
Background: Sport-related head and neck injuries, including concussion, are a growing global public health concern with a need to explore injury risk reduction strategies such as neck exercises. Objectives: To systematically review the literature to investigate: (1) the relationship between neck strength and sport-related head and neck injuries (including sport-related concussion (SRC); and (2) whether neck exercise programs can reduce the incidence of (a) sport-related head and neck injuries; and (b) SRC. Methods: Five databases (Ovid MEDLINE, CINAHL, EMBASE, SPORTDiscus, and Web of Science) and research lists of included studies were searched using a combination of medical subject headings and keywords to locate original studies which reported the association between incidence of head and/or neck injury and neck strength data, or included a neck exercise intervention either in isolation or as part of a more comprehensive exercise program. Results: From an initial search of 593 studies, six were included in this review. A narrative synthesis was performed due to the heterogeneity of the included studies. The results of two observational studies reported that higher neck strength, but not deep neck flexor endurance, is associated with a lower risk of sustaining a SRC. Four intervention studies demonstrated that injury reduction programs that included neck exercises can reduce the incidence of sport-related head and neck injuries including SRC. Conclusion: Consideration should be given towards incorporating neck exercises into injury reduction exercise programs to reduce the incidence of sport-related head and neck injuries, including SRC.